Oral Motor Treatment Efficacy: Feeding and Swallowing Skills in Children with Cerebral Palsy - Maria E. Widman-Valencia; Luis F. Gongora-Meza; Héctor Rubio-Zapata; Rita E. Zapata-Vázquez; Elma Vega Lizama; Marco Ramírez Salomón; Damaris Estrella-Castillo (Behavioural Neurology)
This study is aimed at identifying the relationship between oral motor treatment and the improvement of abilities for feeding and swallowing in boys and girls with CP residing in the state of Yucatán. The sample consisted of 30 patients with a diagnosis of CP and the presence of ADT, with gross motor function levels from II to V, between 3 and 14 years old, of which 50% received oral motor treatment. The predominant diagnosis was spastic CP and tetraplegia. An interview was carried out with the tutor, the application of the gross motor skills scale, and an assessment of feeding skills. The feeding and swallowing skills that improved significantly with the oral motor treatment were mandibular mobility, tongue activity, abnormal reflexes, control of breathing, and general oral motor skills (p≤0.05). Within the sample that did not receive oral motor treatment, 46% presented low or very low weight and 40% referred recurrent respiratory diseases. In the end, it was concluded that feeding skills improve significantly with oral motor treatment, regardless of the severity of gross motor involvement. Likewise, oral motor treatment was associated with a lower presence of respiratory diseases and nutritional compromise.